HR Competency Development Strategy to Increase Company Competitiveness in The Midst of Industrial Revolution 4.0‎ - Safa'atillah, Nurus; H, RR. Ella Evrita; Estiana, Ria; Kusumawati, Berlianingsih; Judijanto, Loso (International Journal of Accounting and Economics Studies, 2025)
The rapid transformation driven by Industrial Revolution 4.0 has brought significant disruption in global business dynamics, confirming ‎the strategic role of Human Resources (HR) in maintaining organizational competitiveness. This study aims to explore a comprehensive HR ‎competency development strategy that is aligned with the technological, structural, and cultural changes triggered by Industry 4.0. Using a ‎qualitative literature review approach, this study analyzed 40 accredited journal articles and empirical studies published between 2019 and ‎‎2024. The findings show that in order to remain competitive, companies need to adopt a dynamic competency framework that emphasizes ‎digital literacy, adaptive leadership, critical thinking, agility, and data-driven decision-making for HR professionals. In addition, the ‎integration of learning technologies such as artificial intelligence (AI)-based training systems and personalized learning platforms has been ‎proven to significantly increase the effectiveness of competency development. The study also highlights the need to transform the role of ‎HR departments from administrative functions to strategic business partners that are able to drive innovation and workforce transformation. ‎This research contributes to the discourse of strategic HR management by proposing a competency development model that is responsive to ‎digital transformation, in order to build organizational resilience and sustainable growth in the Industry 4.0 era‎.
Keywords: Competency Development; Digital Transformation; Human Resources; Industry 4.0; Organizational Competitiveness; Strategic HR ‎Management.